(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
This paper examines blockchain technology and food waste management in the hospitality industry. Food waste prevention is an important issue for hotels, as food consumption is difficult to estimate, often leading to huge amounts of waste. Food waste occurs at each stage of the food supply chain and represents a big percentage of hospitality waste. Although many studies examine the difficulties of food waste management, only a limited number of studies examine the stages of food waste inside food supply chains. The coordination of food supply chains can be supported by blockchain technology, which can break the supply chain into smaller parts and help managers to better mitigate food control. To address these issues, this paper conducts an extensive literature review, firstly to clarify the concept of food waste management in the hospitality industry and secondly to examine the benefits of the use of blockchain technology in food supply chains. Combining the obtained knowledge, this study aims to analyze the relationship between blockchain and food waste management practices. It also aims to examine how this combination boosts hotels to increase their performance and gain customers’ loyalty. Therefore, this paper analyses food waste management in the hospitality industry makes propositions on how blockchain technology could support food waste management in the food supply chain and forms the base for future research.